A SNP-based genome-wide association study (GWAS) of seed-yield related traits in Psathyrostachys juncea using wheat as a reference genome - Zhen Li; Tian Wang; Xiaomin Ren; Feng Han; Yingmei Ma; Lan Yun (PeerJ)
Background Psathyrostachys juncea is an popular perennial grass for both mowing and grazing when used for pasture establishment in high latitude regions. P. juncea has the advantages of high yield, high quality, good palatability and high nutritional value. It is widely used in artificial grassland construction and ecological restoration in Inner Mongolia and other regions. Methods The current study aimed to identify genetic signals associated with seed yield in P. juncea germplasm through a genome-wide association study (GWAS) using wheat as a reference genome. 300 accessions of P. juncea germplasm from different countries were used as materials to assess eight seed yield-related traits in two environments for two consecutive years. Results All the trait values varied considerably across genotypes. Across different locations, the coefficient of variation among genotypes was the highest for seed yield per plant, which exceeded 70%. Further correlation analysis of seed yield factors showed that seed yield per plant had a significant positive correlation with reproductive tiller number. The population exhibited five population structures (Q) assessed by using 84,024 single-nucleotide polymorphisms (SNPs). After controlling Q and K (subgroups), GWAS identified 121 SNPs significantly associated with eight traits. Among them, 19 SNPs were detected in multiple environments, and a total of 91 candidate genes were annotated, which involve the synthesis of cell wall polysaccharides and proteins, plant growth and development, photosynthesis, gibberellin regulation, hormone signal transduction, phenylalanine metabolism, and amino acid metabolism processes. The identification of SNP signals and related candidate genes could enrich the existing genomic resources and lay a foundation for the study of molecular breeding, mapping, and cloning of important genes in P. juncea.